The effect of stoichiometry on the thermal behaviour of synthetic iron-nickel sulfides - Chamberlain, Anthony C. (Curtin University, 1996)
The effect of stoichiometry on the pyrolytic decomposition, oxidation and ignition behaviour of synthetic violarite and pentlandite has been established. These minerals, of general formula (Fe,Ni)(subscript)3S(subscript)4 and (Fe,Ni)(subscript)9S(subscript)8 respectively, may vary considerably in Fe:Ni ratio. Pentlandite can also show some variation in metal:sulfur ratio. A series of samples, ranging in stoichiometry from Fe(subscript)0.96Ni(subscript)1.97S(subscript)4 to Fe(subscript)0.20Ni(subscript)2.72S(subscript)4 and Fe(subscript)5.80Ni(subscript)3.15S(subscript)8 to Fe(subscript)3.40Ni(subscript)5.55S(subscript)8, were synthesised and characterised using wet chemical analysis, electron probe micro-analysis (EPMA), scanning electron microscopy (SEM), X-ray diffraction (XRD), and Brunauer, Emmett and Teller (BET) surface area analysis.The thermal behaviour of these sulfides was examined using simultaneous Thermogravimetry-Differential Thermal Analysis (TG-DTA) at different heating rates and in different atmospheres. Partially reacted samples were collected at various temperatures and analysed using XRD, EPMA, SEM, optical microscopy (OM), and Fourier transform infrared (FTIR) spectroscopy. The endmembers of the violarite and pentlandite series were examined in detail to determine the effect of stoichiometry on the reaction mechanism. In this study the reaction mechanism refers to the sequence of reactions occurring during pyrolytic decomposition or oxidation of the sulfide minerals. Samples were sieved into four particle size fractions, 125-90, 90-63, 63-45 and 45-20 gm, to determine the effect of particle size on the reaction mechanism.When violarite was heated in an inert atmosphere at 10 degrees celsius min(subscript)-1, it initially decomposed to a monosulfide solid solution (mss), (Fe,Ni)(subscript)1-xS, and vaesite, (Ni,Fe)S(subscript)2, indicated by a sharp endothermic peak in the DTA trace. The decomposition temperature was found to be linearly dependent on the iron:nickel ratio, decreasing from 495 degrees celsius to 450 degrees celsius as the iron:nickel ratio decreased from 0.49 to 0.07. This was followed by a broader endothermic peak coinciding with a rapid mass loss, which was associated with the decomposition of vaesite to mss with the loss of sulfur. Between 615-805 degrees celsius the mss was converted to a high temperature form of heazlewoodite, (Fe,Ni)(subscript)3+/-S(subscript)2 melted incongruently at 835 degrees celsius and 805 degrees celsius for Fe(subscript)0.96Ni(subscript)1.97S(subscript)4 and Fe(subscript)0.20Ni(subscript)2.72S(subscript)4 respectively, with further loss of sulfur vapour forming a central sulfide liquid of general formula (Fe,Ni)(subscript)1+xS.Under similar experimental conditions, pentlandite pyrolytically decomposed forming mss and heazlewoodite with no associated loss of sulfur. The decomposition temperature decreased as the iron:nickel ratio deviated from the ideal value of 1:1. A maximum decomposition temperature of 610 degrees celsius was found at an iron:nickel ratio of 1.00, decreasing to 580 degrees celsius at a ratio of 1.84 and 0.61. Sulfur was evolved slowly at temperatures in excess of 760 degrees celsius as mss was converted to heazlewoodite, indicated by a gradual mass loss. The heazlewoodite then melted incongruently in excess of 840 degrees celsius indicated by a sharp endothermic peak, resulting in a further loss of sulfur.The oxidation of violarite and pentlandite was investigated at a heating rate of 10 degrees celsius min(subscript)-1 in an air atmosphere. The oxidation of violarite was initiated by decomposition to mss resulting in a rapid mass loss associated with the evolution of sulfur vapour, and an exothermic peak due to the gas phase oxidation of the sulfur. The iron sulfide component of the mss was then preferentially oxidised to iron(II) sulfate between 485-575 degrees celsius, upon which the sulfate decomposed and the remaining iron sulfide was preferentially oxidised to hematite. The mss core was then converted to (Fe,Ni)(subscript)3+/-xS(subscript)2 between 635-715 degrees celsius, resulting in the loss of further sulfur which was oxidised. The sulfide core, which consisted of predominantly Ni(subscript)3+/-xS(subscript)2 with a minor amount of iron still remaining in solid solution, incongruently melted at a constant temperature of 795 degrees celsius regardless of the initial stoichiometry of the violarite sample. This was followed by the rapid oxidation of the liquid sulfide resulting in a sharp exothermic peak in the DTA trace.For pentlandite, the TG-DTA curve exhibited an initial mass gain commencing at approximately 400 degrees celsius, which was attributed to the preferential oxidation of iron. Evidence from SEM indicated that iron migrated towards the oxygen interface, where it was oxidised to hematite. During this process the metal: sulfur ratio decreased and pentlandite was converted to mss. The iron sulfide component of the mss phase was then preferentially oxidised to hematite as indicated by a major exotherm, which occurred in the temperature range 575-665 degrees celsius, forming an oxide product layer around a nickel sulfide core. The oxidation of the remaining nickel sulfide followed the same reaction sequence to that of violarite.By increasing the heating rate to 40 degrees celsius min(subscript)-1, and carrying out the oxidation in pure oxygen, the tendency of the sulfides to ignite was established. Ignition was characterised by a highly exothermic reaction which coincided with a rapid mass loss over a short time period. Overheating of the samples above the programmed furnace temperature was also observed. Violarite exhibited ignition behaviour while pentlandite did not.Both sulfides were subjected to shock heating conditions (heating rate = 1500 - 5000 degrees celsius min(subscript)-1, oxygen atmosphere) using isothermal thermogravimetry (TG). This method produces heating rates analogous to those which are experienced in the reaction shaft of an industrial flash smelter. The effect of stoichiometry on ignition temperature and extent of oxidation for the entire series of synthetic violarites and pentlandites was determined. Partially ignited and ignited products were collected from isothermal TG experiments and were examined by OM, SEM and EPMA to establish the ignition mechanism.Both violarite and pentlandite ignited using the isothermal TG technique. A clear relationship was found between the stoichiometry of violarite and pentlandite and the ignition temperature, with an increase in the iron:nickel ratio causing a decrease in the ignition temperature. The ignition temperature also decreased as the size of the particles decreased.The extent of oxidation increased as the iron:nickel ratio increased, and also increased as the particle size decreased.